On the move: Mobilome of the Ralstonia solanacearum Species Complex and its role in the fitness, pathogenicity and genome evolution - Gonçalves, Osiel Silva (2019)
Ralstonia solanacearum is one of the most devastating plant pathogenic bacteria found all over the world, capable of infecting a wide diversity of hosts. This soil-borne pathogen is composed of a large-scale group of strains varying in geographical distribution and pathogenic behavior known as R. solanacearum Species Complex (RSSC). In this context, mobile genetic elements may play a significant role in shaping the genetic, and these elements may be important to the bacteria expand their ecological niche or colonize a new host since they promote genetic variability and often carry a cargo gene. In this context, we performed a genome mining in 106 RSSC and 15 Ralstonia spp. genomes and comparative genomic analysis based on Integrative and Conjugative Elements (ICEs), Genomic Islands (GIs), Insertion Sequences (ISs) and Transposons. Our results provided a collective dataset of 41 GIs and 12 ICEs in the RSSC. These elements represent an important fraction of the Ralstonia genomes (1-5%). Phylogenetic analysis showed that the elements are related to geographic origin and species, but there is evidence of genetic flux between isolates belonging to different countries from the Americas and Horizontal Gene Transfer between strains from Asia. ICEs and GIs carry a repertoire of genes with potential impact on Ralstonia fitness and pathogenicity such as stress response and candidate virulence genes as several type III effector proteins which may enable the bacteria to evolve rapidly and infect a wide range of hosts. In addition, we identified 2,957 IS elements in the genome of 59 representative RSSC strains and closely related Ralstonia spp. A unique set of 13 IS families were found highly conserved across the strains, suggesting their ancestral acquisition. We found four novel transposons sequences belong to Tn3 family carrying genes related to antibiotic resistance and avirulence protein as passenger genes. Numerous internal rearrangements events with a subset being associated with IS were demonstrated, indicating the impact of these elements on RSSC genome evolution. We also mapped numerous IS elements interrupting avirulence genes, which provides evidence that IS may be one of the driving forces of RSSC pathogenicity evolution. In conclusion, here we provide a dataset of the mobile genetic elements in one of the most important plant pathogens found all over the world. These data provide novel insights into the RSSC diversified adaptation, opening new paths to a better understanding of the impact of these elements on the genome evolution and pathogenicity of R. solanacearum. Keywords: Genome evolution. Phytopathogen. ICEs. Genomic islands. Insertion Sequence